The Existence of the Female Character Meutia in the Novel Gadis yang Menulis Surat Setiap Malam by Arafat Nur - Mukallalah, Siti Musdalifatul; Istiqomah; Mulyanto; Sucipto; Ni Nyoman Sarmi (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
Existential female characters are the existence of female characters in literary texts. The existence of existentialism in psychology encourages human self-awareness of their existence. In researching the novel The Girl Who Writes Letters Every Night, the aim is to describe the structure of the characters' experiences. The theory used is Rollo May's existentialist psychological theory. Existential psychology is an attempt to understand humans who experience and who are the targets of experience. Descriptive qualitative methods were used in this research with data analysis techniques in the form of listening, reading, taking notes. Then, content analysis uses the content of the quoted text data. The findings include the structure of the characters' experiences regarding: (i) death; (ii) emptiness (loneliness and isolation); (iii) anxiety; (iv) feelings of guilt; (v) togetherness; (vi) spatiality, (vii) temporalis; and (viii) body